Comparisons of the system performance for the small solid oxide fuel cell applications - Jee, Youngseok; Lah, Seyun; Son, Ji-Won; Cha, Suk Won (ELSEVIER SCIENCE BV, 2010)
Among the various sizes of the fuel cell applications, the field of portable power sources shows the best feasibility clue to the pi ice competitiveness Solid oxide fuel cells have various sub system types such as internal reforming/external reforming, single chamber/dual chamber, hydrogen feeding/hydrocarbon feeding and so on We supposed that the performance gaps must exist except the stack performance gaps we calculated many factors on the basis of the mass/species balance. thermal balance and power balance In this study we were able to compare the power efficiency, fuel efficiency and portability from the calculations And we could estimate the operation conditions of each type At the result the hydrogen feeding dual chamber type showed the best performance in most fields of comparison (C) 2009 Elsevier B V All lights reserved